2009
DOI: 10.1002/bdd.648
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of pyrrole‐imidazole polyamides after intravenous administration in rat

Abstract: The pharmacokinetics of pyrrole (Py)-imidazole (Im) polyamides was studied in rats after the intravenous administration of these compounds. Py-Im polyamide (A) was composed of Ac-ImPyPy-ImPyPy-beta-Dp (beta: beta-alanine, Dp: N,N-dimethylaminopropylamide). Py-Im polyamide (B) was composed of Ac-PyIm-beta-ImIm-PyPy-beta-PyPy-beta-Dp. Py-Im polyamide (C) was composed of Ac-PyPy-beta-PyImPy-PyPyPy-beta-ImPy-beta-Dp. The molecular weight of Py-Im polyamide (A) was 1035.12, that of Py-Im polyamide (B) was 1422.51 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…18 In addition, this compound has a different character from other genesilencing tools, such as siRNA or antisense oligo nucleotides, because penetration in the living cells, cytosol import and nuclear transport of PI polyamide occur without any delivery system and may not be influenced by any catabolic enzymes or metabolic enzymes, such as nucleases and P450 enzymes, even in animals. [19][20][21][22] These findings highlight the advantages of PI polyamide as a suitable candidate compound for pre-transcriptional HER2 gene silencing. An earlier publication has also reported that PI polyamide compounds showed specific binding at the Ets-binding site of the HER2/neu promoter region and inhibition of HER2/neu promoter-driven transcription measured in a cell-free system using nuclear extract from a human breast cancer cell line, SKBR-3.…”
mentioning
confidence: 82%
“…18 In addition, this compound has a different character from other genesilencing tools, such as siRNA or antisense oligo nucleotides, because penetration in the living cells, cytosol import and nuclear transport of PI polyamide occur without any delivery system and may not be influenced by any catabolic enzymes or metabolic enzymes, such as nucleases and P450 enzymes, even in animals. [19][20][21][22] These findings highlight the advantages of PI polyamide as a suitable candidate compound for pre-transcriptional HER2 gene silencing. An earlier publication has also reported that PI polyamide compounds showed specific binding at the Ets-binding site of the HER2/neu promoter region and inhibition of HER2/neu promoter-driven transcription measured in a cell-free system using nuclear extract from a human breast cancer cell line, SKBR-3.…”
mentioning
confidence: 82%
“…Moreover, they can be delivered to cells or tissues without using vectors or delivery reagents (Lai et al, 2005). Fukusawa et al (2009) established a high-performance liquid chromatography measurement method for PI polyamide and systematically administered PI polyamide to rats by the parenteral route to evaluate its pharmacokinetic effect and demonstrated that PI polyamides show the same pharmacokinetic effects as regular drugs in serum. Hence PI polyamide is now expected to be a novel medicine that acts as a gene silencer to transcriptionally regulate target diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The LLOQ was determined as 1 µg/mL for both PI polyamides A and B. All of the methods were successfully applied to evaluate the pharmacokinetics of the PI polyamides (Fukasawa et al, 2009;Fukasawa et al, 2007;Nagashima et al, 2009b Intra-assay Inter-assay Matrix Table 1. Intra-and inter-assay accuracy and precision for the determination of PI polyamides A and B in rat plasma and urine.…”
Section: Bioanalyticsmentioning
confidence: 99%